Pelatihan Pembuatan Video Pembelajaran Menggunakan Smartphone bagi Guru MTs Nurul Huda Paowan Situbondo - Nine Febrie Novitasari; David Nurfiqih (Universitas Mathla'ul Anwar Banten, 2022)
Training in Developing Instructional Videos for teachers at MTs Nurul Huda Paowan. During the pandemic, the learning process at MTS Nurul Huda experienced a decline in the quality of learning. This is because the learning system has changed from conventional to online. The limited online learning facilities owned by students make teachers at MTs Nurul Huda not optimal in carrying out learning. The use of learning media for online learning has never been carried out because teachers did not have a good understanding of teaching media and lack the skills to make instructional videos as appropriate teaching media during the pandemic. Therefore, we tried to offer solutions to overcome these problems by providing training on making learning videos using smartphones for MTS teachers Nurul Huda. The implementation of this activity was carried out for approximately a month with the following details: counseling, two training activities, and evaluation. This training utilized the Kinemaster application as an instructional video maker tool for teachers. The evaluation was carried out in two ways, with participants and with team members of the activity. The result of this activity is an increase in teachers' understanding of the importance of teaching media which is marked by their high interest and enthusiasm during the training. In addition, this activity also resulted in an increase in the quality and professionalism of teachers which was marked by the instructional videos they produced.